Post-return stroke VHF electromagnetic activity in north-western Mediterranean cloud-to-ground lightning flashes - A. Kolínská; A. Kolínská; I. Kolmašová; I. Kolmašová; E. Defer; O. Santolík; O. Santolík; S. Pédeboy (Atmospheric Chemistry and Physics)
We investigate properties of the electromagnetic activity following the first lightning return stroke (RS), using concurrent observations from the SLAVIA (Shielded Loop Antenna with a Versatile Integrated Amplifier) sensor, the SAETTA (Suivi de l'Activité Electrique Tridimensionnelle Totale de l'Atmosphère) Lightning Mapping Array (LMA) and the METEORAGE LF (low-frequency) network in the Corsica region. From the data collected between September and December 2015, we selected 66 negative cloud-to-ground (−CG) and 26 positive cloud-to-ground (+CG) lightning flashes in the north-western Mediterranean region. In the SAETTA data, we observe a decrease in the very high frequency (VHF) radiation rate and the VHF power, as recorded within a typical 80 µs time window at the LMA stations, immediately after the RS pulse in 59 −CG flashes. Contrastingly, we show that all examined +CG flashes exhibit a rapid increase in the VHF radiation rate and the VHF power immediately after the RS. We suggest a possible explanation of this phenomenon by considering the step-like propagation of a negative part of the bidirectional leader starting at the top end of the positive lightning channel inside the thundercloud, emitting electromagnetic radiation across a broad frequency spectrum.